App for The Detection of Risk Factors for Cervical Cancer in University Students - Cabrera, Jack Anthony Aguilar; Cabrera, José Alexander Aguilar; Custodio, Paolo Vicente Martell; Custodio, Gian Franco Vicente Martell; Ronceros, Mirko Martín Manrique; Narváez, Carlos Alfredo Gil; Alva, Wilder Leonardo Valverde (South Eastern European Journal of Public Health, 2025)
Expert systems (SE) is an area of Artificial Intelligence that is responsible for studying knowledge-based systems, are applied to many fields such as medicine, military strategies, financial economics, engineering, law and others, you can also say They try to imitate the reasoning of an expert to solve a problem of a defined topic. Their behavior is based on previously defined knowledge and through this knowledge, the SE are able to calculate solutions (Sánchez, 2015). On the other hand; In the world, the first three causes of death in women due to cancer correspond in descending order to breast cancer, lung cancer and cervical cancer with standardized means by age between 11.41 and 6.89 per 100,000 women. The National Statistical Office of the United States of America indicates an approximate number of 10,000 deaths from this disease (Beramendi, 2017). That is why, the objective of this research was to detect the risk factors in cervical cancer in the students of the Universidad Nacional del Santa; not trying to replace the specialist doctor, but supporting him in giving a reliable diagnosis, fast and using information technologies. The results showed the reliability of the information that allows an early diagnosis of cervical cancer. Therefore, it is recommended to expand the field of research of expert systems to cover a greater number of diseases.